Synthesis of cordierite from bagasse ash - T.saengchantara, Wanna; Junlar, Pranee; Rugthaicharoencheep, Sansanee; Sriprasertsuk, Sutthima (Bulletin of Applied Sciences, 2014)
This research presents the results of a cordierite synthesis from bagasse ash. The formulas were calculated using a tri-axial table by varying the amount of MgO, AI2O3., and SIO2 in the range of 9-17%, 30-38%, and 47-55%, respectively. The selected raw materials were mixed using bagasse ash, magnesite, kaolin, and alumina and fired at 1250 and 1300 °C to form a cordierite phase. The structures were analyzed using powder X-ray diffraction (XRD) method. A formula with the highest cordierite phase was selected to form samples and then fired at 1300°C. The physical properties, i.e., firing shrinkage, water absorption, bulk density, modulus of rupture (MOR), and coefficient of thermal expansion (COE) were studied. The samples yielded firing shrinkage of 8.6%, water absorption of 8.4%, bulk density of 2.09 g/cm3, MOR of 48.9 MPa, and COE of 3.53x10-6 / °C.experimental body fried at 1200 °C was found its ability to absorb the liquid at a certain level and to release the fragrance.